Micro-Architecture Survey and Modeling: the Archetype of Messina’s Ancient Municipal City Hall (diségno, 2024)
The subject of this paper concerns the wooden model of the ancient municipal building of the city of Messina. The building, embedded within the eighteenth-century Palazzata, was demolished due to the damages caused by the 1908 earthquake. The only iconographic documentation that has come available to us, despite the vintage photos, refers to the surveys made by J.I. Hittorff in 1823 and to this artifact, realized in a scale of 1:38 and dating back to 1810, currently kept at the Regional Interdisciplinary Museum ‘Maria Accascina’ in Messina. A sort of inverse operation will be carried out: a physical model of a work that no longer exists will be surveyed and overlapped and compared with the survey drawings mentioned; after verifying any discrepancies on the compositional, geometric and dimensional features, an attempt will be made to evaluate the aesthetic and functional qualities. The model survey will be carried out both with photogrammetry across the alignment of a series of images taken on the object and the creation of the sparse and dense cloud (Agisoft Metashape) or by point cloud acquisition from laser scanner. Once this investigation phase is over, with the current 3D printing methods, a new model conforming to the original, but in a smaller scale, could be assembled, constituting an effective tool for the usability of a visually impaired audience as well.
Keywords: instrumental survey; modelling; archetype; ancient municipal hall of Messina